Comparing the effectiveness of Acceptance and Commitment Therapy (ACT) and Compassion Focused Therapy (CFT) on tension headaches and blood pressure in women with somatic symptom disorder - Sadeghi Nisiani, Sara; Ghanifar, Mohammad Hassan; Shahbazizadeh, Fatemeh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Compassion Focused Therapy (CFT) on tension headaches and blood pressure in patients with physical symptoms disorder. Methods: This was a quasi-experimental study with a pre-test, post-test and follow-up design with a witness group. The statistical population of the research included all women with physical symptoms disorder who referred to Sara counseling centers and Imam Zaman (AS) Helping Association in Isfahan city in the first half of 2021. And then, justifying the objectives of the research and having the consent to participate in the research, they were randomly placed in two experimental and control groups. The data were obtained using headache questionnaire and blood pressure measurement and were analyzed by repeated measurement analysis method and SPSS software. Results: The results showed that the treatment based on acceptance and commitment (ACT) was effective on tension headaches, systolic blood pressure and diastolic blood pressure (p < 0.05). But compassion-focused therapy (CFT) was effective only on tension headaches (p